Treptacantha abies-marina (S.G. Gmelin) Kützing: Characterization and Application as a Whole Food Ingredient. Issue 10 (25th November 2020) - Afonso, C.; Guarda, I.; Mourato, M.; Martins, L.L.; Fonseca, I.; Gomes, R.; Matos, J.; Gomes, A.; Bandarra, N.M.; Cardoso, C.
ABSTRACT: The brown seaweed Treptacantha abies-marina is an abundant resource still undervalued. Novel products incorporating this seaweed were prepared: a 3%, w/w, Treptacantha abies-marina cookie (Tpc Ck) and a 2%, w/w, Treptacantha abies-marina sauce (Tpc Sc), which were compared with a control cookie (Ctl Ck) and a control sauce (Ctl Sc), respectively. The proximate composition, elemental composition, and phenolic content as well as the antioxidant activity, as measured by 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid (ABTS), 2, 2-diphenyl-1-picrylhydrazyl (DPPH), and Ferric Ion Reducing Antioxidant Power (FRAP) methods, of the used seaweed and control and Tpc-enriched nutraceutical products were determined. The bioaccessibility was assessed through an in vitro digestive model. Sauces and cookies differed in their elemental composition, being K, Ca, Mg, Na, P, and Zn concentrations higher in the sauces. The addition of seaweed biomass affected the As concentration, which increased from 4.8 ± 0.7 to 40.4 ± 2.7 mg/kg dw and from 3.7 ± 0.2 to 15.9 ± 1.3 mg/kg dw, for sauces and cookies, respectively. On the basis of FRAP and ABTS, sauces, and especially Tpc Sc, yielded aqueous extracts more antioxidant than the cookies. Antioxidant activity enhancement by seaweed incorporation was stronger in the cookies. Elemental bioaccessibility was high, 100% for Ca, Mg, and Na.